From sea to shore - meeting the challenges of the sea : (Coasts, Marine Structures and Breakwaters 2013) - Allsop, N. W. H. 1951-; Burgess, Kevin (ICE Publishing, 2014)
The ICE Coasts, Maritime Structures and Breakwaters conference series, sponsored by the ICE for over thirty years, is the leading international forum for the presentation of the latest developments in coastal and maritime structures. The tenth conference was the largest in the history of the series attracting over 450 delegates and 130 papers across 3 plenary and 27 parallel sessions. In addition to the papers presented, these proceedings retain the tradition of including full discussions from each session.